EFFECT OF OPERATING PATTERNS ON THE EFFECTIVENESS OF LAW ENFORCEMENT IN THE SEA - Rully Tri Anggoro (JOURNAL ASRO, 2019)
Indonesian Navy as a Security Task Force at Sea tasked with arranging marine security operations seeks to reduce the crime rate at sea. However, in carrying out marine operations there are still many illegal fishing, illegal logging, pollution, narcotics smuggling, piracy, people smuggling and sea accidents at various points in the sea. Koarmada II. Koarmada II in supporting the demand for operations that are under the command of its control, will be adjusted to the readiness of the existing elements, because not all elements below are in a condition ready for operation, there are several elements that must carry out maintenance and repair. Therefore we need the right operating pattern strategy in increasing the effectiveness of law enforcement at sea. The purpose of this research is to find out the right Indonesian Navy Operation Pattern in increasing the effectiveness of law enforcement at sea and the effect of the Operational Pattern on the effectiveness of sea law enforcement carried out by Indonesian Navy. Using the multiple regression analysis method, the results show that the Indonesian Navy Operational Pattern consisting of Patrol Operation Pattern (X1), Standby Operating Pattern (X2) and Air Maritime Patrol Operation Pattern (X3) has a real influence on the effectiveness of law enforcement at sea (Y ). The Air Maritime Patrol Operation Pattern (X3) has the greatest coefficient in influencing the Effectiveness Level of law enforcement at sea due to the use of the Air Maritime Patrol Operation Pattern so that it can explore the area very efficiently and effectively, thereby increasing opportunities to find violations of Law at sea.Keywords: Operational Patterns, Effectiveness of Law Enforcement, Multiple Regression analysis.